Adult‐onset noncirrhotic hyperammonemic encephalopathy probably caused by splenorenal shunts. Issue 4 (25th April 2022) - Yoshizawa, Kazuhiro; Yonezawa, Naoki; Takei, Tetsuhiro; Sugiki, Kei
Abstract: This case illustrates adult‐onset noncirrhotic hyperammonemic encephalopathy, which is most likely caused by splenorenal shunts and is a rare but potentially fatal cause of altered mentation in the critical care setting. Splenorenal shunts should be considered as a differential in cases of hyperammonemic encephalopathy without liver cirrhosis. Abstract : Adult‐onset noncirrhotic hyperammonemic encephalopathy is a rare but potentially fatal cause of altered mentation in the critical care setting. Splenorenal shunts should be considered as a differential in cases of hyperammonemic encephalopathy without liver cirrhosis.